SNOW BALLING METHOD ABOUT HIGH RISK PREGNANCY FOR INCREASING PREGNANT WOMEN'S KNOWLEDGE - Alina Rosa Riadi; Ika Yudianti; Endah Kamila Mas’udah (AIPKIND (Asosiasi Pendidikan Kebidanan Indonesia), 2022)
High risk pregnancy is one of the contributors to AKI. This is due to a lack of knowledge about high-risk pregnancies. Efforts to provide information through health education with more innovative methods such as snow balling are expected to increase the knowledge of pregnant women about high-risk pregnancies. Lack of knowledge of pregnant women increases MMR due to high risk pregnancies. This study aims to determine the effect of health education on the snow balling method on the knowledge of pregnant women about high-risk pregnancies. The research design used quantitative research with quasi-experimental methods, pretest and posttest designs with a control group. The sample in this study used a total sampling technique of 32 respondents. Data collection was done by dividing the respondents into 2 groups, namely the treatment group (snow balling) and the control group (lecture). The results of statistical tests using the Wilcoxon Signed Rank Test obtained a value of = 0.139 (ρ> 0.05), which means that there is no effect of health education on the snow balling method on the knowledge of pregnant women about high-risk pregnancies. Based on the research results, the provision of health education can be carried out in various methods, both using the snow balling method and the lecture method which can increase the knowledge of pregnant women about high-risk pregnancies